2020
DOI: 10.1021/acs.energyfuels.0c01242
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Aging Processes in Bitumen at the Molecular Level with High-Resolution Fourier-Transform Ion Cyclotron Mass Spectrometry and Two-Dimensional Gas Chromatography Mass Spectrometry

Abstract: Bitumen is a highly viscous and chemically complex petroleum-derived material, which is applied as a binder in road construction. However, the asphalt undergoes hardening, cracking, and embrittlement not only due to oxidative short-term aging during the mixing and paving process but also due to long-term aging during the service time of the pavement. In this study, chemical changes occurring during short-term aging, mimicked by a prolonged rotating flask procedure, are investigated for an artificial bitumen mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 69 publications
1
40
0
Order By: Relevance
“…As ionization technique, atmospheric pressure chemical ionization (APCI) was applied, which covers semi-polar to polar compounds expected to be present in the solubility fractions. It's value for analyzing complex mixtures in combination with TG-FT-ICR MS has been demonstrated in previous studies [33,44,51]. Here, we showed that TG-FT-ICR MS can address the controversial issue of the predominant structural motif of asphaltenes exhibiting corresponding results to previous studies on the same asphaltenes with DI-IRMPD-FT-ICR MS [48,50].…”
Section: Introductionsupporting
confidence: 81%
“…As ionization technique, atmospheric pressure chemical ionization (APCI) was applied, which covers semi-polar to polar compounds expected to be present in the solubility fractions. It's value for analyzing complex mixtures in combination with TG-FT-ICR MS has been demonstrated in previous studies [33,44,51]. Here, we showed that TG-FT-ICR MS can address the controversial issue of the predominant structural motif of asphaltenes exhibiting corresponding results to previous studies on the same asphaltenes with DI-IRMPD-FT-ICR MS [48,50].…”
Section: Introductionsupporting
confidence: 81%
“…45 However, Neumann et al (2020) observed a decrease in the presence of carbazol groups after aging bitumen. 46 This result shows that carbazol is a thermally stable compound; however, it can act as a reagent in certain compounds present in asphalt. This may be an indication for future studies showing the influence of nitrogen groups, even thermally stable compounds, on asphalt aging.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Carbazole is used in the synthesis of thermally stable polymers as an electron donor . However, Neumann et al (2020) observed a decrease in the presence of carbazol groups after aging bitumen . This result shows that carbazol is a thermally stable compound; however, it can act as a reagent in certain compounds present in asphalt.…”
Section: Resultsmentioning
confidence: 99%
“…The isomeric diversity of heavily alkylated constituents hinders a more targeted approach. Collision-induced dissociation (CID) is known for dealkylation of petroleum constituents. , Without the selection of a precursor, so-called all-ion fragmentation can be used as a valuable approach for the structural description of the dominant aromatic core structures. , Structural description of the aromatic core is crucial for a variety of applications, such as the design of refining processes or in understanding flow/deposition and aggregation properties of asphaltenes, a high aromatic fraction of petroleum. , …”
Section: Resultsmentioning
confidence: 99%
“…11,57 Without the selection of a precursor, so-called all-ion fragmentation can be used as a valuable approach for the structural description of the dominant aromatic core structures. 57,58 Structural description of the aromatic core is crucial for a variety of applications, such as the design of refining processes or in understanding flow/deposition and aggregation properties of asphaltenes, a high aromatic fraction of petroleum. 47,52 Here, the concept of all-ion fragmentation is deployed as follows: The whole ion mixture is fragmented by collisioninduced dissociation (CID) applying a voltage of 75 V to the trap gas cell.…”
Section: ■ Results and Discussionmentioning
confidence: 99%